Schematized meaning of the concept of percent by the 14 year-olds children - Nik Abdul Rahman, Nik Suryani (EuroJournals Publishing, Inc., 2010)
Based on the theory of constructivism, this study identified 14 year old’ schematized meaning of the concept of percent and how the children use them in solving the related problems. Data incorporating both verbal and non-verbal behaviour was gathered from seven 14 year-olds based on five successive clinical interview sessions involving several problematic activities. Findings revealed that children gave meaning to percent based on fraction, whole number and mixed numbers. Fractional and whole number schemes were used to give meaning to percents less than one hundred and percents greater than one hundred respectively. Mixed number scheme was used specifically to give meaning to percents greater than one hundred. Each scheme was used by the children in several given situations during the interview sessions. Further, the children’s mental images of percent were mainly based on either fractional or whole number ideas, and they dominantly use continuous regions rather than discrete regions in representing percent. It is therefore suggested that mathematics teachers learn the mathematical knowledge of their students to harmonize their teaching methods with the nature of the children’s knowledge